A qualitative evidence synthesis of healthcare professionals' experiences and views of palliative care for patients with a haematological malignancy. (9th September 2020) - Dowling, Maura; Fahy, Paul; Houghton, Catherine; Smalle, Mike
Abstract: Introduction: Patients with haematological malignancies may not be receiving appropriate referrals to palliative care and continuing to have treatments in the end stages of their disease. This systematic review of qualitative research aimed to synthesise healthcare professionals' (HCPs) views and experiences of palliative care for adult patients with a haematologic malignancy. Methods: A systematic search strategy was undertaken across eight databases. Thomas and Harden's approach to thematic analysis guided synthesis on the seventeen included studies. GRADE‐GRADEQual guided assessment of confidence in the synthesised findings. Results: Three analytic themes were identified: (a) "Maybe we can pull another 'rabbit out of the hat', " represents doctors' therapeutic optimism, (b) "To tell or not to tell?" explores doctors' decision‐making around introducing palliative care, and (c) "Hospice, home or hospital?" describes HCPs concerns about challenges faced by haematology patients at end of life in terms of transfusion support and risk of catastrophic bleeds. Conclusion: Haematologists value the importance of integrated palliative care but prefer the term "supportive care." Early integration of supportive care alongside active curative treatment should be the model of choice in haematology settings in order to achieve the best outcomes and improved quality of life.